Reducing green tape or rolling back IA in Australia: What is each jurisdiction up to? - Middle, Garry; Clarke, B.; Franks, D.; Brown, L.; Kellet, J.; Lockie, S.; Morrison-Saunders, A.; Pope, Jennifer; Glasson, John; Harris, E.; Harris-Roxas, B. (IAIA, 2013)
EIA has been practiced in Australia and the rest of the world for over 40 years, but despite its successes, EIA may now be facing its biggest challenge since it came into being in 1970 with the US National Environmental Policy Act. As Morgan (2012, 11) notes: "As governments look to stimulate economic growth and create employment in response to the current financial crisis, many are promoting a major expansion of physical infrastructure, encouraging resource development projects, and generally seeking to speed decision-making about development projects. Both EIA and SEA should be even more important in such circumstances, yet the moves taken in some countries to speed up decision-making may weaken the provisions for environmental protection, including impact assessment." In this political and economic environment, EIA is under scrutiny. Proposed changes to the EU directive on EIA released in October 2012 contain ten changes to the Articles of the Directive, with six of these referring to either ‘streamlining’ EIA or introducing specific timeframes for parts of the EIA process (European Commission 2012). This scrutiny has not been restricted to economies in recession, but includes those that have avoided recession because of strong resources sectors.The same appears to be happening in Australia, and this paper reports on these and other possible 'efficiency' changes to EIA in Australia at both national and sub-national levels. We attempt to critically examine the nature of such changes and the risks that may be associated with their implementation. Changes to three of the sub-national EIA processes are reviewed in detail, as well as the proposed changes to the national EIA process.There is always room for more timely assessments, but a critical examination of the potential consequences of these "reforms" on the conduct of EIAs is needed, including whether these efficiency changes will deliver sound environmental management and sustainability-oriented decision-making.